Interpretation of the Meaning of Mosque Architecture : A Case Study Mosque 99 Cahaya in Lampung, Sumatera Island, Indonesia - Salura, Purnama; Clarissa, Stephanie (International Journal of Engineering and Technology, 2018)
This research traced the relationship that exists between the expressions of mosque architecture with the meaning created. The method used for this research is: Firstly, recording building which is based on the theory about the scope of the building. Secondly, described the entire composition and building properties. Thirdly, interpreted the meaning that is created both on the outside and in the view of the space inside. Based on the results of the analysis, it can be concluded that the outside architectural form of the mosque tends to be interpreted as an abstract monument. While itâ€™s inner space interpreted as a shelter that has nothing to do with its function as a religious building. This research is expected to give theoretical contribution to the knowledge of architecture that is by formulating new method to interpret expression of architectural form in general and specifically on the mosque architecture. While in practice, this research could be used as a reference in designing mosque architecture. In addition to scientific and architectural practices, this research could be used as a source of knowledge and offered an alternative perspective for the wider community in appreciating the work of architectureÂ Â